Vibrations inside buildings due to subway railway traffic. Experimental validation of a comprehensive prediction model - Lopes, Patrícia (2016)
The present paper focuses on the experimental validation of a numerical approach previously proposed by the authors for the prediction of vibrations inside buildings due to railway traffic in tunnels. The numerical model is based on the concept of dynamic substructuring and is composed by three autonomous models to simulate the following main parts of the problem: i) generation of vibrations (train-track interaction); ii) propagation of vibrations (track-tunnel-ground system); iii) reception of vibrations (building coupled to the ground). The experimental validation consists in the comparison between the results predicted by the proposed numerical model and the measurements performed inside a building due to the railway traffic in a shallow tunnel located in Madrid. Apart from the brief description of the numerical model and of the case study, the main options and simplifications adopted on the numerical modeling strategy are discussed. The balance adopted between accuracy and simplicity of the numerical approach proved to be a path to follow in order to transfer knowledge to engineering practice. Finally, the comparison between numerical and experimental results allowed finding a good agreement between both, fact that ensures the ability of the proposed modeling strategy to deal with real engineering practical problems.